Risk of low birth weight on adulthood hypertension - evidence from a tertiary care hospital in a South Asian country, Sri Lanka: a retrospective cohort study - Dileepa Senajith Ediriweera; Nuwani Dilina; Usha Perera; Francisco Flores; S. Samita (BMC, 2017)
Abstract Background Although low birth weight (LBW) is common in South Asian region there are not many studies being done to evaluate LBW and adulthood hypertension association in this region, including in Sri Lanka. Although this association has been studied in other regions, most studies have not evaluated this association in the presence of socioeconomic and lifestyle factors. This study was conducted to investigate whether low birth weight (LBW) is associated with adulthood hypertension after adjusting for other potential risk factors of hypertension. Methods Nearly 15,000 individuals born during 1950 to 1965 were selected and invitations were sent to their original addresses. Out of them 217 individuals responded and among them birth weight was recovered for 122 individuals. Separate linear logistic models were fitted to model high systolic blood pressure (SBP: systolic blood pressure > 140 mmHg), high diastolic blood pressure (DBP: diastolic blood pressure > 90 mmHg) and hypertension (either SBP > 140 mmHg or DBP > 90 mmHg). Results Separate linear logistic model fitting revealed LBW having a significant association with high SBP (OR = 2.89; 95% CI: 1.01 to 8.25; P = 0.04), and hypertension (OR = 3.15; 95% CI: 1.17 to 9.35; P = 0.03), but not with high DBP (OR = 0.75; 95% CI: 0.22 to 2.16; P = 0.62), when effect of LBW was studied after adjusting for all other potential risk factors. Conclusions LBW has a tendency to cause high adult blood pressure in South Asian region, and the findings are consistent with previous work on LBW and adulthood hypertension association in other regions of the world.